Pengaruh Konsentrasi Inisiator terhadap Pembentukan Poli Tanin sebagai Zat Warna Pada Dye Sensitized Solar Cell (DSSC) - Widi Feronika; Hardeli Hardeli (Departemen Kimia FMIPA UNP, 2022)
Dye Sentized Solar Cell (DSSC) is a third generation solar cell that uses dyes to absorb photons from sunlight which will be converted into electrical energy. This research aims to produce a high efficiency of the dye used. The dye in DSSC must have a large number of double bonds to absorb photons because the more photons that are converted into electrical energy, the higher the resulting efficiency. Polymerization is one of the methods used to increase π bonding in dyes. Polimerization is the combination of several monomers. The monomer used in this research is tannin. Tanin are organic compounds that have double bonds.Tannin polymerization uses a crosslinked agent glutaraldehyde to produce polytannin which are used for staining in DSSC. The assembled DSSC will be tested for resistance and voltage using a digital multimeter. Dye will be characterized using FT-IR, the results of the FT-IR test are carried out to confirm the formation of polytannins which are characterized by the presence of metylene groups formed. The efficiency obtained is higher than that the of the unpolymerized tannin dye , which is 7,3% efficiency.